Day at the museum. A benchmarking and feasibility study for large group, one‐session exposure treatment for spider phobia. (17th July 2019) - Li, Sophie H.; Newby, Jill; Graham, Bronwyn M.
Abstract: Background: In vivo exposure therapy for specific phobia is an effective treatment, yet up to 80% of individuals with specific phobia go untreated. This appears to be due to an unwillingness to confront the feared stimulus and a lack of appropriate service provision. One‐session treatment (OST) for specific phobias is an efficacious form of in vivo exposure that is well accepted by its recipients; however, few clinicians are trained, or willing, to deliver this approach. Aims: The current study aimed to determine the feasibility, acceptability and effectiveness of OST delivered to a large group in a naturalistic community setting. Method: Spider phobic individuals were recruited from the community for an open trial of OST delivered in groups of 15 individuals at the Australian Museum using resources from their spider exhibition. Outcome measures (Spider Phobia Questionnaire, Behavioural Approach Task) were administered immediately before and again immediately after OST (Behavioural Approach Task), or at one‐week post‐treatment (Spider Phobia Questionnaire). Within‐group effect sizes on outcomes were benchmarked against previous studies of individual and small group OST for spider phobia to determine the relative effects of this program. Results: Fear and avoidance of spiders were significantly reduced, and these outcomes compared well with individual and small group OST outcomes from previous studies. Conclusions: Large group OST is a feasible resource‐effective method of providing treatment for spider phobia.